Nutritional, lifestyle and environmental factors in ocular hypertension and primary open‐angle glaucoma: an exploratory case–control study. (6th March 2012) - Renard, Jean‐Paul; Rouland, Jean‐François; Bron, Alain; Sellem, Eric; Nordmann, Jean‐Philippe; Baudouin, Christophe; Denis, Philippe; Villain, Max; Chaine, Gilles; Colin, Joseph; de Pouvourville, Gérard; Pinchinat, Sybille; et al.
Abstract: Purpose:  To evaluate known and potential risk factors, including nutritional, lifestyle and environmental factors, differentiating patients with high‐tension primary open‐angle glaucoma (POAG) from control subjects with ocular hypertension (OHT). Methods:  In 2006–2007, 111 French ophthalmologists prospectively enrolled 339 cases of POAG and 339 age‐matched controls with OHT. After a clinical examination with assessment of ocular risk factors, the ophthalmologist filled, during face‐to‐face interview, a detailed questionnaire developed by nutritionists and epidemiologist on lifestyle and environmental risk factors, including socio‐demographic variables, dietary habits related to omega‐3 fatty acids intake, smoking and alcohol drinking and professional exposure to pesticides and other chemicals. Associations of POAG with risk factors were estimated using conditional logistic regression, with adjustment for age, gender and duration of disease. Results:  In the final multivariate model, by comparison with OHT, POAG was significantly associated with more frequent use of pesticides during the professional life [OR = 2.65, 95% confidence interval (CI): 1.04–6.78, p = 0.04] and with low consumption of fatty fish (OR = 2.14, 95% CI: 1.10–4.17, p = 0.02) and walnuts (OR = 2.02, 95% CI: 1.18–3.47, p = 0.01). POAG was also associated with higher frequency of heavy smoking (40 pack‐years or more, OR = 3.93, 95% CI: 1.12–13.80, p = 0.03) but not with moderate (20–40 pack‐years) and light smoking (<20 pack‐years). Conclusions:  These exploratory observations suggest a protective effect of omega‐3 fatty acids and a deleterious effect of heavy smoking and professional exposure to pesticides in POAG. This will need to be confirmed in future studies.